The development of a self-help toolkit: a hybrid approach to PCT and Visual Journaling for Prolonged Grief Disorder Volume 2 - Elis Syuhaila Mokhtar (2019)
The thesis presents the findings of practice-led research arising from the development of a self-help toolkit. The toolkit comprises a hybrid of person-centred therapy (PCT) and visual journaling, and is aimed at individuals suffering from prolonged grief disorder (PGD) resulting from the loss of the loved one (WHO, 2015; APA, 2013). PCT is renowned for providing an affectionate facilitation to develop a therapeutic relationship between counsellors/therapists and clients/patients (Rogers, 1957; 1965; BAPCA, 2018), while visual journaling is a current self-help approach that uses images and, occasionally, words to record an individuals emotions and daily life experiences for self-expression, self-discovery and self-reflection (Capacchione, 1977, 2015; Ganim & Fox, 1999; Hieb, 2005). The central research question driving this project concerned bringing together those two different methods: How is it possible to bridge the core concerns of PCT and visual journaling to develop a productive hybrid of both in the form of a self-help toolkit that provides a therapeutic environment for its users? This thesis charts the development process of this hybrid toolkit. Through practice-led research, autoethnography, user-centred design and qualitative analysis, two prototypes were initiated and tested (non-clinically) with volunteers from the general public who had experienced loss. The research design and methods used are presented within the thesis in five progressive phases. Phase 1 is the process of developing and formulating the hybrid approach by testing it on myself: practices included deploying PCT's conditions of being honest and positive and having a compassionate conversation while exploring current feelings through visual journaling (STAGE 1 trial). Phase 2 involved conducting an autoethnographic study to design the toolkits first prototype. Phase 3 involved testing the toolkit on a group of nine volunteers recruited from the university network (STAGE 2 trial). Phase 4 refined the toolkit using a user-centred approach to evaluate participants feedback and develop the second prototype to be more interactive and user-friendly: including a step-by-step approach for instructions and one-by-one demonstrations, especially how to draw while engaging in a compassionate conversation. Phase 5 examined the refined toolkit by conducting two further trials: the first of these was with a group of five volunteers from the previous (STAGE 3 trial), while the final trial involved a group of seven volunteers in collaboration with the local community arts organisation, Charnwood Arts, in Loughborough, Leicestershire (STAGE 4 trial). The results of each of these stages of development, testing and refinement have demonstrated that the toolkit answers the projects central question and provides an effective hybrid of PCT and visual journaling for potential therapeutic purposes. Significantly, the practical outcome of this thesis has been to design a toolkit that is the first visual journaling workbook to take a PCT approach designed specifically for PGD. The toolkit has the potential to enrich a persons empathy and to become self-compassionate: thereby enhancing their quality of life. The methodology used in the project, as well as the non-clinical results of the trials, demonstrate that the toolkit is beneficial for health and well-being. This is an important area in current research at the nexus of the creative arts and sciences and that is a further key context for this project. Future research is recommended by collaborating with clinicians or counsellors/therapists to conduct a clinical trial to test the toolkit on those with a clinical diagnosis of PGD.